Lactate trafficking inhibition restores sensitivity to proteasome inhibitors and orchestrates immuno‐microenvironment in multiple myeloma. Issue 4 (15th February 2023) - Barbato, Alessandro; Giallongo, Cesarina; Giallongo, Sebastiano; Romano, Alessandra; Scandura, Grazia; Concetta, Saoca; Zuppelli, Tatiana; Lolicato, Marco; Lazzarino, Giacomo; Parrinello, Nunziatina; Del Fabro, Vittorio; Fontana, Paolo; et al.
Abstract: Metabolic changes of malignant plasma cells (PCs) and adaptation to tumour microenvironment represent one of the hallmarks of multiple myeloma (MM). We previously showed that MM mesenchymal stromal cells are more glycolytic and produce more lactate than healthy counterpart. Hence, we aimed to explore the impact of high lactate concentration on metabolism of tumour PCs and its impact on the efficacy of proteasome inhibitors (PIs). Lactate concentration was performed by colorimetric assay on MM patient's sera. The metabolism of MM cell treated with lactate was assessed by seahorse and real time Polymerase Chain Reaction (PCR). Cytometry was used to evaluate mitochondrial reactive oxygen species (mROS), apoptosis and mitochondrial depolarization. Lactate concentration resulted increased in MM patient's sera. Therefore, PCs were treated with lactate and we observed an increase of oxidative phosphorylation‐related genes, mROS and oxygen consumption rate. Lactate supplementation exhibited a significant reduction in cell proliferation and less responsive to PIs. These data were confirmed by pharmacological inhibition of monocarboxylate transporter 1 (MCT1) by AZD3965 which was able to overcame metabolic protective effect of lactate against PIs. Consistently, high levels of circulating lactate caused expansion of Treg and monocytic myeloid derived suppressor cells and such effect was significantly reduced by AZD3965. Overall, these findings showed that targeting lactate trafficking in TME inhibits metabolic rewiring of tumour PCs, lactate‐dependent immune evasion and thus improving therapy efficacy. Abstract : One of the hallmarks of multiple myeloma (MM) is metabolic changes of malignant plasma cells (PCs) and adaptation to tumour microenvironment (TME). The metabolic reprogramming of MM cells shapes TME towards a hypoxic, acid and nutrient depleted niche, thereby supporting tumour proliferation and immune evasion. Malignant PCs are known to secrete lactate and we previously demonstrated that mesenchymal stromal cells from MM patients are more glycolytic than same cells from healthy donors. Hence, we aimed to explore the impact of high lactate concentration on cellular metabolism of tumour PCs and efficacy of the proteasome inhibitors.